Bioequivalence study of tablet forms of risperidone, olanzapine and quetiapine in healthy volunteers - V. V. Pisarev; M. M. Ulyashova; K. A. Vdovin; N. I. Tiseyko (Фармакокинетика и Фармакодинамика)
This article presents the results of three studies of bioequivalence tablet forms of atypical antipsychotics risperidone, olanzapine, and quetiapine produced by JSC «Northern Star», Russia and the corresponding original drugs risperidone, olanzapine and quetiapine. Studies have been done by determining the concentrations of risperidone, olanzapine and quetiapine in the blood plasma of healthy volunteers after a single dose compared drugs inside an empty stomach open randomized crossover design in two stages, with two sequences medication. Plasma samples were analyzed by validated volunteers using HPLC with mass spectrometric detection. Analyzed for drugs following pharmacokinetic parameters were calculated: Сmax , AUC0-t , AUC0-? „ Сmax /AUC0-t TSmax , kel , T1/2. 90% confidence intervals relations for log-transformed values ??of AUC0-t, Cmax and Smax/AUC0-t study drugs risperidone were respectively 91,39-112,98%, 91,12-105,02%, 88,69-104,50% and the study drugs olanzapine 89,32-121,29%, 95,79-114,68%, 87,11-116,42% and in the study drugs quetiapine 93,24-115,84%, 90,03-120,80% and 92,96-108,33%. According to studies, it was concluded bioequivalence compared drugs risperidone, olanzapine and quetiapine.